ANALISIS IMPORTANCE-PERFORMANCE: EVALUASI KUALITAS LAYANAN BALAI DIKLAT INDUSTRI (Arthavidya Jurnal Ilmiah Ekonomi, 2022)
Abstract: Industrial Training Center as a technical implementation unit in the field of industrial education and training that is under and responsible for the Head of the Industrial Education and Training Center has the task of implementing Education and training for industrial human resources. Training participants as the object of service recipients basically have an important role, especially in terms of providing criticism and suggestions for evaluating Surabaya Education Training Center services primarily by evaluating expectations and satisfaction with services.This study combines the service quality model and importance-performance analysis to evaluate the services provided by the Surabaya Education Training Center. The questionnaire was distributed to 130 training participants to measure the level of expectation (expection) and performance (perceived) of the services provided by the Surabaya Education Training Center. The results of the study show that all services provided by the Surabaya Industrial Training Center have not met the expectations of the students with the tangible aspect which ranks highest with an average mean value of -0.542. Importance-Performance analysis shows there are 13 aspects in quadrant I as organizational competitive advantage and 3 aspects in quadrant IV as the main weaknesses of the organization. Keywords: Service Quality, SERVQUAL, Importance-Performance Analysis Abstrak: Balai2Diklat Industri sebagai3unit pelaksana5teknsiidi bidang pendidikanidanipelatihan industri yang berada dibawah danibertanggung jawabiKepala Pusat Pendidikan daniPelatihan Industri memiliki tugas untuk melaksanakan Pendidikan dan pelatihan bagi sumber daya manusia industri. Peserta diklat sebagai objek penerima layanan pada dasarnya memiliki peranan penting terutama dalam hal memberikan kritik dan saran untuk mengevaluasi layanan Balai Diklat Industri Surabaya terutama dengan mengevaluasi harapan dan kepuasan terhadap layanan.Penelitian ini menggabungkan model kualitas layanan dan analisis importance-performance untuk mengevaluasi layanan yang disediakan oleh Balai Diklat Industri Surabaya. Kuesioner dibagikan kepada 130 peserta diklat untuk mengukur tingkat harapan (expection) dan kinerja (perceived) dari pelayanan yang diberikan oleh Balai Diklat Industri Surabaya. Hasil Penelitian menunjukan bahwa seluruh layanan diberikan Balai Diklat Industri Surabaya belum memenuhi harapan dari para peserta didik dengan aspek tangible yang menempati urutan tertinggi dengan nilai rata-rata mean sebesar -0.542. Analisa Importance-Performance menunjukan terdapat 13 aspek pada kuadran I sebagai keunggulan kompetitif organisasi dan 3 aspek pada kuadran IV sebagai kelemahan utama organisasi. Kata kunci: Kualias Pelayanan, SERVQUAL, Importance-Performance Analysis